FPGA-based real-time simulation for EV station with multiple high-frequency chargers based on C-EMTP algorithm - Zirun Li (Protection and Control of Modern Power Systems, 2020)
Abstract The electric vehicle (EV) charging station is a critical part of the infrastructure for the wide adoption of EVs. Real-time simulation of an EV station plays an essential role in testing its operation under different operating modes. However, the large numbers of high-frequency power electronic switches contained in EV chargers pose great challenges for real-time simulation. This paper proposes a compact electromagnetic transient program (C-EMTP) algorithm for FPGA-based real-time simulation of an EV station with multiple high-frequency chargers. The C-EMTP algorithm transforms the traditional EMTP algorithm into two parallel sub-tasks only consisting of simple matrix operations, to fully utilize the high parallelism of FPGA. The simulation time step can be greatly reduced compared with that of the traditional EMTP algorithm, and so the simulation accuracy for high-frequency power electronics is improved. The EV chargers can be decoupled with each other and simulated in parallel. A CPU-FPGA-based real-time simulation platform is developed and the proposed simulation of the EV station is implemented. The control strategy is simulated in a CPU with 100 μs time-step, while the EV station circuit topology is simulated in a single FPGA with a 250 ns time-step. In the case studies, the EV station consists of a two-level rectifier and five dual-active bridge (DAB) EV chargers. It is tested under different scenarios, and the real-time simulation results are validated using PSCAD/EMTDC.